2010
DOI: 10.1523/jneurosci.6365-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Representation of the Pitch of Harmonic Complex Tones in the Auditory Nerve

Abstract: The pitch of harmonic complex tones plays an important role in speech and music perception and the analysis of auditory scenes, yet traditional rate-place and temporal models for pitch processing provide only an incomplete description of the psychophysical data. To test physiologically a model based on spatiotemporal pitch cues created by the cochlear traveling wave (Shamma, 1985), we recorded from single fibers in the auditory nerve of anesthetized cat in response to harmonic complex tones with missing fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
66
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 70 publications
3
66
0
Order By: Relevance
“…When comparing isolate tone tasks with tone sequencing, both groups had more right matches at the isolate tone task and, for the NMG, the sequencing task turned out to be more difficult ( Table 3), showing that it seems that musical learning, either formal or informal, helps the individual to overcome this greater difficulty that is the sound sequencing (13)(14)(15)(16)(17) . This fact corroborates the study that concluded that the longer the sequence of auditory stimuli for the sequencing task, the more difficult the activity becomes, since it involves a greater number of auditory abilities (12) and a greater auditory processing refinement (21) . Many people that do not sing in tune process musical information correctly, however they are unable to produce a desired tone.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When comparing isolate tone tasks with tone sequencing, both groups had more right matches at the isolate tone task and, for the NMG, the sequencing task turned out to be more difficult ( Table 3), showing that it seems that musical learning, either formal or informal, helps the individual to overcome this greater difficulty that is the sound sequencing (13)(14)(15)(16)(17) . This fact corroborates the study that concluded that the longer the sequence of auditory stimuli for the sequencing task, the more difficult the activity becomes, since it involves a greater number of auditory abilities (12) and a greater auditory processing refinement (21) . Many people that do not sing in tune process musical information correctly, however they are unable to produce a desired tone.…”
Section: Discussionsupporting
confidence: 89%
“…The administration procedure of the Pitch-matching Scanning included the discrimination and vocal reproduction of isolate tones and the temporal ordination of some tones, always by means of dichotic listening. This procedure involves the physiologic mechanism of discrimination of sound patterns related to the temporal ordination abilities (non-verbal gnostic process) (12) . Musicians had more right matches for isolate tones than non-musicians (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One attractive alternate model uses a synergistic approach, relying on the spatial pattern of temporal information (Shamma, 1985). Recently, Cedolin and Delgutte (2010) provided the first physiological evidence that spatiotemporal information from auditory nerve responses can be used to extract pitch.…”
mentioning
confidence: 99%
“…To test the spatiotemporal pitch model, Cedolin and Delgutte (2010) recorded singleunit responses to harmonic complex tones from the auditory nerve of anesthetized cats. Given the difficulty in finely sampling neighboring auditory nerve fibers with single-unit recordings, Cedolin and Delgutte (2010) instead used the property of scaling invariance, where local spatiotemporal response patterns can be inferred from the response of a single auditory nerve fiber.…”
mentioning
confidence: 99%